A multi-layered illustration of exemplary business ethics practices with voices of the engineers in the health products industry - Kim, Dayoung (Journal of business ethics, 2023)
Promoting ethical practice within an organization has been a continuous challenge in the business ethics community. To enrich organizational practices for promoting business ethics across an organization, this paper aims to introduce the voices of practitioners working in organizations that offer exemplary practices. Based on semi-structured interviews with 21 engineers working in the health products industry, we identified 12 pervasive ethical values that we grouped to four categories: fiduciary, economic, engineering, and process values. As ethics has been embraced as a core element of the ethical practice of our study participants regardless of their rankings and roles in their organizations, we investigated organizational strategies for promoting ethical practice. We identified four categories of organizational strategies: symbols, memberships, practices, and systems. Each strategy affected the 12 ethical values in different ways. Lastly, we identified three characteristics of the industry contexts that appeared to influence ethical values: customer impact, economic norms, and highly regulated industry. We discuss how the findings from this paper can potentially promote new discussions and practices in the business ethics community.